The aesthetic world of Golden Horde literature and its continuity in Kazakh literature - Sabyr Мұрат; Ramanova Айгуль; Kussainova Дина; Akhmetov Талгат (Turkic Studies Journal, 2024)
The written literary monuments of the Golden Horde era hold significant importance in the spiritual and cultural history of the Kazakh people. The common spiritual culture of the Turkic peoples during this period was embodied in a unified Middle Turkic language, which laid the foundation for literature in the Kipchak-Oghuz and Oghuz-Kipchak languages and marked the emergence of national trends. However, these literary monuments also show the influence of Eastern poetic traditions, which are clearly manifested in Qutb’s “Khosrow and Shirin”, and Khorezmi’s “Mukhabbat-name”. The purpose of this paper is to study the world of spiritual and cultural values, including aesthetic knowledge, within the context of written literary heritage. Additionally, a number of artistic and aesthetic concepts in Kazakh literature, which have deep roots, are considered. The written literary heritage of the Golden Horde period reflected the worldview, artistic and aesthetic expression through linguistic means, including the use of epithets, metaphors, comparisons, idioms and set phrases. The written monuments of the 13th–14th centuries constitute a rich source of information regarding the spiritual and cultural worldview and aesthetic perception of the period. The research has significant practical value. The results obtained can be used in the history of literature and cultural studies.